1, 25-Dihydroxyvitamin D3 Altered Metabolism of MCF10A-ras Cells Decreases Viability in Extracellular Matrix Detached Conditions (FS13-05-19). (13th June 2019) - Sheeley, Madeline; Teegarden, Dorothy; Wong, Katie
Abstract: Objectives: Metastasis is the main cause of most breast cancer related deaths. Throughout the process of metastasis, cancer cells strive to survive in conditions where they are detached from the extracellular matrix (ECM). Vitamin D may play a role in preventing breast cancer metastasis by modulating metabolism in breast cancer cells detached from ECM. Here we hypothesize that the active metabolite of vitamin D, 1, 25-dihydroxyvitamin D3 (1, 25D), regulates the metabolism of breast cancer cells, and decreases their viability in ECM detached conditions. Methods: The Harvey -ras transformed MCF10A human breast epithelial cell line (MCF10A- ras ) were utilized for these studies. Poly-HEMA coated plates were used to model ECM detachment paired with MTT assays to measure cell viability. Viability is measured in cells treated with vehicle (ethanol) or 10 nM 1, 25D and maintained in varying nutrient concentrations. mRNA expression of metabolic genes is quantified using qPCR and, triacylglycerol (TAG) is quantified using a Wako Diagnostics colorimetric assay. Results: Results show that 1, 25D treatment decreases viability in detached conditions by 23%. Glutamine deprivation also decreases viability in detached conditions by 40%. In addition, in combination 1, 25D treatment and glutamine deprivation results in a 71% decrease in viability. These results imply that while glutamine is required for ECM survival, 1, 25D's modulation of metabolism is targeted elsewhere. Further, when compared to vehicle, 1, 25D treated cells have a 45% increased TAG accumulation prior to plating in detached conditions. A 50% decrease was observed in mRNA expression of the enzyme pyruvate carboxylase (PC), and replenishing the product of PC and tricarboxylic acid (TCA) cycle intermediate oxaloacetate rescues detached cell viability in glutamine deprived conditions by 84%. Conclusions: These results demonstrate the important role energy metabolism plays in cell survival during ECM detachment. Furthermore, our results suggest that 1, 25D regulation of metabolism may sensitize breast cancer cells to ECM detachment death. We conclude that cells detached from ECM require flux into the TCA cycle in order to survive, and 1, 25D's downregulation of PC contributes to the observed decrease in viability following 1, 25D treatment. Funding Sources: National Institute of Health and USDA.